2008
DOI: 10.1128/jvi.00429-08
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Changes Induced by Bovine Papillomavirus Type 1 in Equine Fibroblasts

Abstract: Bovine papillomavirus type 1 (BPV-1) and, less commonly, BPV-2 are associated with the pathogenesis of common equine skin tumors termed sarcoids. In an attempt to understand the mechanisms by which BPV-1 induces sarcoids, we used gene expression profiling as a screening tool to identify candidate genes implicated in disease pathogenesis. Gene expression profiles of equine fibroblasts transformed by BPV-1 experimentally or from explanted tumors were compared with those of control equine fibroblasts to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 65 publications
(73 reference statements)
1
31
0
Order By: Relevance
“…The gene for MMP1 is overexpressed in HPV-associated cervical cancer and in BPV-1-associated equine sarcoids (Narayan et al, 2007;Yuan et al, 2008), but the papillomavirus proteins involved in the transcriptional activation of the MMP1 gene in these tumours have not yet been identified. MMP9 too has been reported to be activated by papillomavirus (Akgül et al, 2006; Behren et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene for MMP1 is overexpressed in HPV-associated cervical cancer and in BPV-1-associated equine sarcoids (Narayan et al, 2007;Yuan et al, 2008), but the papillomavirus proteins involved in the transcriptional activation of the MMP1 gene in these tumours have not yet been identified. MMP9 too has been reported to be activated by papillomavirus (Akgül et al, 2006; Behren et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, MMP1 was present in much greater amounts than in HaCaT-pCI-neo cells and also in suprabasal layers (Fig. 3l), indicating that the abundant production of MMP1 by the HaCaT-16E5 cells was not only due to the interaction with type I collagen but also predominantly to the effect of E5.E5-induced invasion might substantially contribute to tumour progression in persistently infected cervical epithelial cells, although this remains to be confirmed.The gene for MMP1 is overexpressed in HPV-associated cervical cancer and in BPV-1-associated equine sarcoids (Narayan et al, 2007;Yuan et al, 2008), but the papillomavirus proteins involved in the transcriptional activation of the MMP1 gene in these tumours have not yet been identified. MMP9 too has been reported to be activated by papillomavirus (Akgül et al, 2006; Behren et al, 2005).…”
mentioning
confidence: 99%
“…Equine MMP-1 and Fra-1 mRNAs were quantified by real-time relative quantification RT-PCR. The relative quantification RT-PCR primer and probe sets for MMP-1 and Fra-1 gene and the housekeeping gene glyceraldehyde 3-phosphate dehydrogenase (GAPDH) have been described previously (Yuan et al, 2008b). Total RNA extraction, cDNA synthesis and PCR conditions were all as described previously (Yuan et al, 2007b).…”
Section: Methodsmentioning
confidence: 99%
“…The upregulation of endogenous MMP-1 expression by E5 was surprising given the inability of E5 to stimulate the MP0.2 promoter, and suggested either that E5 impacts on the activity of the fulllength MMP-1 promoter or that it upregulates MMP-1 expression by indirect mechanisms (see below). Previously, we found that BPV-1 upregulated the transcriptional expression of Fra-1 (Yuan et al, 2008b). In this study, we examined the expression of phosphorylated (activated) Fra-1 (p-Fra-1) by immunoblotting and immunofluorescence staining using a specific antibody against p-Fra-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation